From Fardhu Kifayah to Micro Social Security System: Reproduction of Mechanical Solidarity in The Management of Funeral Equipment in Pakem Village - Faizuna, Lela (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
This study analyzes the management of funeral equipment and corpse preparation in Pakem Village as a transformation of religious obligation into a community-based micro social security system. Using a qualitative approach through in-depth interviews, observation, and documentation, the research explores how fardhu kifayah is institutionalized as a structure of social solidarity beyond its normative-ritual dimension. The findings show that funeral management is understood not merely as a family responsibility but as a collective duty organized through shared equipment inventories, communal contributions, local traditions such as klitikan, and active youth involvement. This practice reflects Émile Durkheim’s concept of mechanical solidarity, where shared religious values foster collective consciousness and social integration, while also illustrating Max Weber’s value-oriented action (wertrational) in the community’s voluntary participation beyond minimal obligations. Functionally, the system operates as a micro social security mechanism by facilitating risk sharing, redistributing resources, and reducing the financial burden on grieving families. Rather than diminishing traditional solidarity, village administrative modernization has encouraged adaptive cross-generational collaboration and strengthened the integration of religious values with local norms. The sustainability of this system depends on public trust, youth engagement, and the internalization of religious values as a source of collective moral legitimacy, confirming that death practices serve as an adaptive informal social welfare infrastructure in contemporary rural contexts.